2020
DOI: 10.1002/1878-0261.12619
|View full text |Cite
|
Sign up to set email alerts
|

The noncoding function of NELFA mRNA promotes the development of oesophageal squamous cell carcinoma by regulating the Rad17‐RFC2‐5 complex

Abstract: Recently, RNAs interacting with proteins have been implicated in playing an important role in the occurrence and progression of oesophageal squamous cell carcinoma (ESCC). In this study, we found that NELFA mRNA interacts with Rad17 through a novel noncoding mode in the nucleus and that the aberrant expression of USF2 contributed to the upregulation of Rad17 and NELFA. Subsequent experiments demonstrated that the deletion of NELFA mRNA significantly decreased ESCC proliferation and colony formation in vitro. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…RFC2, being the subunits of RFCs, located within the human chromosomal segments 7q11.23, plays a part in DNA replication repair and cell cycle checkpoint pathway (14,48). There were many studies about RFC2 and certain cancers, most of which stated that RFC2 was obviously upregulated in cancer tissues (19,28,52,53,54). Ho et al (27).…”
Section: Discussionmentioning
confidence: 99%
“…RFC2, being the subunits of RFCs, located within the human chromosomal segments 7q11.23, plays a part in DNA replication repair and cell cycle checkpoint pathway (14,48). There were many studies about RFC2 and certain cancers, most of which stated that RFC2 was obviously upregulated in cancer tissues (19,28,52,53,54). Ho et al (27).…”
Section: Discussionmentioning
confidence: 99%
“…RFC2 plays an important role in the elongation of primed DNA templates by DNA polymerase δ and ε (18). Upregulated RFC2 expression has been associated with a number of cancers, such as nasopharyngeal (19) and esophageal squamous cell carcinoma (20). However, to the best of our knowledge, only a single study has reported the involvement of RFC2 in GBM, in which RFC2 was indicated to enhance temozolomide (TMZ) cytotoxicity (21).…”
Section: Microrna-744-5p Inhibits Glioblastoma Malignancy By Suppressing Replication Factor C Subunitmentioning
confidence: 99%